DEKONSTRUKSI MITOS WAYANG RAMAYANA DAN BARATA YUDA DAN NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL KITAB OMONG KOSONG KARYA SENO GUMIRA AJIDARMA DAN PERANG KARYA PUTU WIJAYA - Tjahjono Widijanto (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2023)
As the title suggests, the purpose of this study is to examine the deconstruction of the myths of wayang Ramayana and Barata Yuda as well as the character values contained in the novels Kitab Omong Blank and the novel War. The discussion is carried out using the characteristics of deconstruction with the result that in The Book of Nonsense, War and War a critical view of the satriya myth is voiced. Rama, Laksamana and Pandawa in the novel are no longer in accordance with the myth of the perfect wayang satriya which represents truth, straight and strong, but reckless, evil and ridiculous. The results of the study show that the myths in wayang have been dismantled and deconstructed by Seno Gumira and Putu Wijaya to uncover and express views and appreciation of the problems of today's socio-cultural life by incorporating character values in the form of: (a) courage, patriotism and love of the land water; (b) humanity/compassion (empathy, caring, helpful), (c) inspirational, fair, patient, honest, disciplined, cooperative, and tolerant.